DAMPAK KEBIJAKAN RELOKASI PASAR TRADISIONAL RAWAJAYA DI WILAYAH KOTA TOBELO KABUPATEN HALMAHERA UTARA - MANZANARIS, MARSEKALDO RIVALDO; RARES, JOYCE; KIYAI, BURHANUDDIN (JURNAL ADMINISTRASI PUBLIK, 2018)
Based on the results of research observations, the researcher sees that there are still manycomplaints from the community and market traders following the Rawajaya traditional market relocationpolicy in Tobelo district of North Halmahera Regency resulting in public problems seen based on indicatorsof policy impact such as Impact on people involvement, impact on out-of-target group, impact on timedimension, Impact on direct costs and Impact on indirect costs, therefore the purpose of this research is toknow the impact of Rawajaya traditional market relocation policy in Tobelo city of North HalmaheraRegency, this research uses research method qualitative descriptive, research informants are 12 (twoelf)informants consisting of 1 head of Industry Office, 1 head of department of Industry and Trade, 4 markettraders, and 6 people divided from 3 districts in Tobelo City region. Data collection techniques used areinterview techniques, observation and dokumentasi. And data analysis techniques used are data reductiontechniques, data presentation, and conclusions drawing.Based on the results of research through several points in the research method, about the impactof Rawajaya traditional market relocation policy in the area of Tobelo city of North Halmahera Regencywhich is seen from the indicators of policy impact. Whereas the impact of Rawajaya's traditional marketrelocation policy can hurt the traders as the target group of policy, because after the traditional market ofRawajaya has been relocated resulting in decreasing merchant income where the lonely market location ofthe customers and accessibility to the new market location also harms the public which is considered toodifficult and the transportation cost is also expensive so that the impact of this policy is very broad coveringcommunity activities as consumers in new markets as well as merchant groups.Keywords: Policy Impact, Traditional Market Relocation